Addition of tanshinone IIA to UW solution decreases skeletal muscle ischemia-reperfusion injury - Wang Hong-gang; Li Zhi-yong; Liu Xiao-lin (Acta Pharmacologica Sinica, 2016)
Aim: To investigate whether tanshinone IIA could improve the effect of UW solution for skeletal muscle preservation and to determine the dose range of tanshinone IIA providing optimal protection during ischemia and reperfusion. Methods: Ischemic rat limbs were perfused with UW solution or UW plus tanshinone IIA (UW+T, 0.05, 0.1, or 0.2 mg/mL) for 0.5 h before reperfusion; controls (I/R) received no perfusion. Serum creatine phosphokinase (CPK), aspartate aminotransferase (AST), and lactate dehydrogenase (LDH) were measured pre-ischemia and after reperfusion (2-h, 4-h, and 6-h). Muscle water content, superoxide dismutase (SOD), malondialdehyde (MDA), adenosine triphosphatase (ATPase) were assessed pre-reperfusion and after 6-h reperfusion. Intercellular adhesion molecule-1 (ICAM-1) and apoptosis were detected after 6-h reperfusion. Reperfusion blood flow was monitored during reperfusion period. Results: UW and UW+T prevented luxury perfusion during reperfusion and inhibited ICAM-1 expression and apoptosis after 6-h reperfusion. Serum CPK, AST, and LDH levels in UW rats were significantly less than those in controls after 2-h reperfusion (no difference, 4-h or 6-h reperfusion). After 4-h ischemia, there were significant differences in water content, MDA, SOD, and ATPase between UW and controls, but no difference after 6-h reperfusion. All tests with UW+T rats were significantly different from control results at corresponding durations. Higher tanshinone doses improved results. Conclusion: UW plus tanshinone IIA increased protection against I/R injury, suggesting that tanshinone IIA has clinical value.